The Procne’s Mētis. On Aeschylus’ Supplices 57-61 (Minerva, 2019)
At the beginning of Aeschylus’ Supplices, the choir of Danaids alludes briefly to the Tereus and Procne’s myth. The text, ambiguous syntactically, has been interpreted in different ways. Our proposal bases on a meticulous analysis of mētis, key word of the passage, that compares both mythic stories, the crime of Danaus’ daughters and that of Tereus’ wife.
Keywords: Aeschylus; Mētis; Translation Studies